Sustained silencing peanut allergy by xanthopurpurin is associated with suppression of peripheral and bone marrow IgE-producing B cell - Yang, Nan; Srivastava, Kamal; Chen, Yujuan; Li, Hang; Maskey, Anish; Yoo, Patrick; Liu, Xiaohong; Tiwari, Raj K.; Geliebter, Jan; Nowak-Wegrzyn, Anna; Zhan, Jixun; Li, Xiu-Min (Frontiers in Immunology, 2024)
Introduction: Peanut allergy is an immunoglobulin E (IgE) mediated food allergy. Rubia cordifolia L. (R. cordifolia), a Chinese herbal medicine, protects against peanut-induced anaphylaxis by suppressing IgE production in vivo. This study aims to identify IgE-inhibitory compounds from the water extract of R. cordifolia and investigate the underlying mechanisms using in vitro and in vivo models. Methods: Compounds were isolated from R. cordifolia water extract and their bioactivity on IgE production was assessed using a human myeloma U266 cell line. The purified active compound, xanthopurpurin (XPP), was identified by LC-MS and NMR. Peanut-allergic C3H/HeJ mice were orally administered with or without XPP at 200µg or 400µg per mouse per day for 4 weeks. Serum peanut-specific IgE levels, symptom scores, body temperatures, and plasma histamine levels were measured at challenge. Cytokines in splenocyte cultures were determined by ELISA, and IgE + B cells were analyzed by flow cytometry. Acute and sub-chronic toxicity were evaluated. IL-4 promoter DNA methylation, RNA-Seq, and qPCR analysis were performed to determine the regulatory mechanisms of XPP. Results: XPP significantly and dose-dependently suppressed the IgE production in U266 cells. XPP significantly reduced peanut-specific IgE (>80%, p <0.01), and plasma histamine levels and protected the mice against peanut-allergic reactions in both early and late treatment experiments (p < 0.05, n=9). XPP showed a strong protective effect even 5 weeks after discontinuing the treatment. XPP significantly reduced the IL-4 level without affecting IgG or IgA and IFN-γ production. Flow cytometry data showed that XPP reduced peripheral and bone marrow IgE + B cells compared to the untreated group. XPP increased IL-4 promoter methylation. RNA-Seq and RT-PCR experiments revealed that XPP regulated the gene expression of CCND1, DUSP4, SDC1, ETS1, PTPRC, and IL6R, which are related to plasma cell IgE production. All safety testing results were in the normal range.Conclusions: XPP successfully protected peanut-allergic mice against peanut anaphylaxis by suppressing IgE production. XPP suppresses murine IgE-producing B cell numbers and inhibits IgE production and associated genes in human plasma cells. XPP may be a potential therapy for IgE-mediated food allergy.